Effects of verbal knee alignment instructions on knee kinematics, kinetics and the performance of a single-leg jump in female adolescent soccer players - Grooten, W. J. A.; Karlefur, O.; Conradsson, D. (European Journal of Physiotherapy, 2020)
Background: Little is known about the effects of verbal instructions on the technique and performance of sports-related tasks. The aim of this study was therefore to investigate the acute effects of knee alignment instructions on knee kinematics and the performance of a single-leg jump in female adolescent soccer players.